Creep properties of siltstone-like materials with different unloading confining pressures under seepage - Zhang, Xiangdong; Zhou, Zhongchao; Yang, Jianjun; Pang, Shuai; Geng, Jie; Li, Wenliang; Zhang, Xuefeng (Frontiers in Earth Science, 2022)
Deep enclosing rocks exhibit non-homogeneous characteristics of dense joints and fissure development. Soft rocks subjected to multiple factors, such as high stress and hydrostatic pressure, are prone to damage and significant deformation, which can lead to instability of the surrounding rocks, failure of the supporting structure, and other accidents. In this study, we investigated the creep behaviour of deep soft rocks and siltstone-like materials subjected to different unloading confining pressures coupled with a high stress field and seepage. Subsequently, the laws and behaviours of parameters, such as the transient strain, creep deformation, and creep rate were derived and analysed under various conditions. The results indicate that the radial creep curve exhibits a variation pattern similar to that of the axial creep. However, the extent of radial creep exceeds that of axial creep in soft siltstone-like rocks under unloading confining pressure conditions. We derived expressions for the constitutive relation of siltstone-like specimens under various unloading confining pressure conditions in the presence of seepage using an improved viscoelasticmodel that considered the coupling effect of fissure and seepage flow. The correlation coefficients of the calculated model values with the experimental values, as obtained by the non-linear least-squares fitting, were all above 0.9178, indicating that the proposed model can accurately characterise the creep process in fissured siltstone.